CRITICAL LEVELS AND DOSES OF MAXIMUM TECHNICAL EFFICIENCY OF PHOSPHORUS IN Handroanthus heptaphyllus SUBJECTED TO PHOSPHORUS FERTILIZATION - Berghetti, Álvaro Luís Pasquetti; Araujo, Maristela Machado; Da Silva, Leandro Souza; Bueno, Jean Michel Moura; Stefanello, Lincon Oliveira; Brunetto, Gustavo (Floresta, 2024)
Tropical and subtropical soils do not always provide the necessary amount of phosphorus (P) to supply the nutrient demand of native trees, such as Handroanthus heptaphyllus (Mart.) Mattos (Ipê-roxo). Therefore, it becomes necessary to apply phosphate fertilizers. However, decision-making and doses to be applied will be more assertive if P’s critical levels (NC) in the soil and leaves and doses of maximum technical efficiency (MET) are defined to improve the fertilizer recommendation system for native trees. The study aimed to propose NC and MET of P in H. heptaphyllus submitted to P application. The experiment was conducted in Red Argisol submitted to the application of five doses of P (0, 20, 40, 80, and 160 kg ha-1). After 24 months of planting, the P content in the soil and its concentration in the leaf tissue, height growth (H) and stem diameter (DC), chlorophyll A fluorescence, and acid phosphatase enzyme activity were determined. The NC in soil and leaves were calculated. The addition of phosphorus fertilization increased the P levels in the soil and leaves, promoting higher H and DC in the H. heptaphyllus plants. The greater availability of P reduced photochemical energy losses by fluorescence. The NC in the soil for growth variables height and stem diameter was 20.0 and 21.2 mg dm-3. The CN in leaves for growth and physiological parameters was, on average, 1.6 g kg-1.